Factors Affecting Productivity of Oil Palm Plantation Harvesters at PT. Bahruny Basilam Langkat District: Faktor-faktor yang Memengaruhi Produktivitas Pekerja Pemanen Perkebunan Kelapa Sawit di PT. Bahruny Basilam Kabupaten Langkat - Ajriya Ghulba (Jurnal Penelitian Kesmasy, 2025)
Labor productivity plays a crucial role in the palm oil plantation sector. This study aimed to examine the influence of several factors on the productivity of palm oil harvesters at PT Bahruny Basilam, Langkat Regency. The variables assessed included age, education level, years of service, nutritional status, number of dependents, and premiums. Adopting a cross-sectional design with a quantitative approach, 60 respondents were selected through simple random sampling. Data collection was carried out using questionnaires and interviews, while multiple linear regression at a 0.05 significance level was applied for analysis. The results indicate that premiums (p-value 0.001) and nutritional status (p-value 0.000) significantly affect labor productivity, whereas age, education, years of service, and number of dependents show no significant influence.